IMPLEMENTATION OF PRACTICUM-BASED SETS MODELS TO IMPROVE PRIMARY SCHOOL STUDENTS' UNDERSTANDING OF CONCEPTS - Nisa, Zahirotun; Uswatun, Din Azwar; Sutisnawati, Astri; Amalia, Arsyi Rizqia (Jurnal Cakrawala Pendas, 2024)
This research aims to describe the implementation of the SETS model in improving concept understanding and describe the increase in concept understanding after learning using the SETS model. The method used is Classroom Action Research (CAR), the design used is the Kemmis and Mc Taggart model, implemented in two cycles. Each cycle consists of planning, implementing actions, observing and reflecting. The participants in this research were 26 class V students at SDN 06 Cisande, consisting of 15 boys and 11 girls. Data collection techniques use observation and test techniques. The results of research on the application of the SETS model during the pre-cycle of teacher and student activities were 25% in the poor category. In cycle 1, teacher activities with an average score of 67% were in the good category, while student activities with an average score of 65% were in the good category. Then it increased in cycle II, teacher activity with an average score of 81 got the very good category and student activity with an average score of 80 got the very good category. The results of research on understanding pre-cycle concepts show completeness of 25%. Then it increased in cycle I to reach 50% completeness. Meanwhile, in cycle II, the results showed that completion reached 86%. Understanding of concepts taken from group practicum method scores, Pre-cycle UAS scores were only 25% in the good category, cycle I after applying the practicum-based SETS model was 58% in the quite good category. In cycle II it became 85% in the very good category. Based on these two cycles, it can be seen that there is an increase in teacher and student activity as well as students' understanding of concepts by implementing the practicum-based SETS model.